Imaging and clinicopathological characteristics of breast cancer among women under the age of 40 years - Mustafa, Abdullateef A.; Hasan, Nada A.; Khalel, Enam A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: although breast cancer in young women is less common and often overlooked, it is still considered a major health concern.Objectives: to evaluate the demographic, clinical, radiological and histopathological characteristics of breast cancer among a sample of Iraqi women diagnosed under the age of 40 years.Patients and methods: a retrospective study enrolled 73 females below the age of 40 years with a history of breast cancer. All data was extracted from an established information system database designed by the Principal Investigator of the Iraqi National Breast Cancer Research Project under supervision of the International Agency for Research on Cancer (IARC) over a 4-years period from 2011 to 2014.Results: seventy three women under the age of 40 years with breast cancer were included in the study out of 625 diagnosed cases at different ages (11.68%). The age at presentation ranged from 25 to 39 years, the peak age frequency (63%) was recorded in the period between 35-39 years (n=46). Family history of breast cancer was noticed in approximately 31.5% of cases (n=23). Early menarche (less than 12 years old) was detected in 78.1% (n=57) of cases. On examination, 90.4% (n=66) of patients had painless palpable breast lump. By Sonography, the lesions were spiculated margins in 52% (n=38) of patients and echogenic halo around the mass was detected in 57.5% (n=42) of cases. Stage-II disease was recognized in 54.8% (n=40) of sample of the study and majority of the tumor (98.6%) were ductal in origin. According to Scarf-Bloom-Richardson method, 60.3% (n=44) of the tumors were moderately differentiated (i.e. grade- II). Eight patients (10.9%) were presented with triple receptor-negative breast cancer and recurrence of tumor was encountered in 17.8% (n=13) of cases.Conclusions: The current study suggest that breast cancer among young Iraqi women under 40 years had high incidence rate but might be less aggressive than what is reported in western countries despite of high recurrence rate.